2014
DOI: 10.1016/j.biortech.2013.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bacillus sp. strains capable of decomposing alkali lignin and their application in combination with lactic acid bacteria for enhancing cellulase performance

Abstract: Effective biological pretreatment method for enhancing cellulase performance was investigated. Two alkali lignin-degrading bacteria were isolated from forest soils in Japan and named CS-1 and CS-2. 16S rDNA sequence analysis indicated that CS-1 and CS-2 were Bacillus sp. Strains CS-1 and CS-2 displayed alkali lignin degradation capability. With initial concentrations of 0.05-2.0 g L(-1), at least 61% alkali lignin could be degraded within 48 h. High laccase activities were observed in crude enzyme extracts fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 33 publications
5
64
1
3
Order By: Relevance
“…These results were in agreement with previous research which showed that pure cellulose has better thermal stability than lignocellulosic fibers (Chang et al 2014). Therefore, the chemical compositions of pulp were the main criteria in deciding the thermal stability of pulp.…”
Section: Table 4 Algebraic Expressions Of Functions Of the Most Commsupporting
confidence: 83%
“…These results were in agreement with previous research which showed that pure cellulose has better thermal stability than lignocellulosic fibers (Chang et al 2014). Therefore, the chemical compositions of pulp were the main criteria in deciding the thermal stability of pulp.…”
Section: Table 4 Algebraic Expressions Of Functions Of the Most Commsupporting
confidence: 83%
“…Similarly, Bacillus sp. strains CS-1&CS-2 removed 61% of lignin (Chang et al 2014). In another finding that corroborated to this work, 50% and 55% of lignin were degraded by Citrobacter freundii and Serratia marcescens, respectively.…”
Section: Periodic Monitoring Of Modified Media Degradation By Axenic supporting
confidence: 75%
“…strain CS-1 (3.5 U/L) and CS-2 (3.0 U/L). These strains showed very low MnP activity (data not shown), while LiP activity was not observed (Chang et al 2014). In contrast to the results obtained in present study, Lai and co-worker worked on thermophilic lignin-degrading bacteria and reported that out of ten isolates CLMT 18 (0.7475 U/ml) and CLMT 34 (0.8178 U/ml) showed the maximum laccase activity, while CLMT5 (1.8759 U/ml), CLMT 18 (1.6684 U/ ml) and CLMT 20 (1.5322 U/ml) showed maximum MnP activity (Lai et al 2017).…”
Section: Periodic Monitoring Of Modified Media Degradation By Axenic mentioning
confidence: 99%
“…Most recently, some efforts have been done to find effective methods to degrade lignin for value-added biofuels and chemicals production, including enzymatic degradation (Chen et al, 2012) alkali pyrolysis (Guo et al, 2014), hydrothermal conversion (Barbier et al, 2012), electrochemical degradation (Tolba et al, 2010), biological degradation (Chang et al, 2014), photocatalytic degradation (Prado et al, 2013), etc. Among them, photocatalysis is considered as an environment friendly and promising technology due to excellent merits such as clean, effective, energy-saving, and low cost.…”
Section: Introductionmentioning
confidence: 99%